If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -7 = 35 + -1t Reorder the terms: -7 + 5t = 35 + -1t Solving -7 + 5t = 35 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -7 + 5t + t = 35 + -1t + t Combine like terms: 5t + t = 6t -7 + 6t = 35 + -1t + t Combine like terms: -1t + t = 0 -7 + 6t = 35 + 0 -7 + 6t = 35 Add '7' to each side of the equation. -7 + 7 + 6t = 35 + 7 Combine like terms: -7 + 7 = 0 0 + 6t = 35 + 7 6t = 35 + 7 Combine like terms: 35 + 7 = 42 6t = 42 Divide each side by '6'. t = 7 Simplifying t = 7
| a^2-17=-42 | | 11-4*5= | | 0.75x=6.66 | | 205-2x=43x+20 | | 6w^2-18w-108=0 | | h=-16t^2+52t | | 4x^2-9x+11=7x+4 | | 3x+1=9.6 | | -8(2b+1)+(17b-7)=0 | | 3w^2+8w+5=0 | | 9.6=3x+1 | | 12-9x=107-44x | | x^2+6=7 | | 25=-3 | | x^2+3x-30=7x+2 | | 121-2x=34x+21 | | 4x+37=9x-47 | | 13=-6+1 | | -3+2=-7x-22 | | 0=5-2y | | 11x-9=123 | | 5x-y=-20 | | 3-4(x+5)-7=3+2(4-2x)-16 | | (8x-7)(4x+1)= | | 2(4d+5c)= | | 20=5+x | | x*6+94=x*10-6 | | (8c-3d)= | | a-b=-35 | | 98-6x=21x+23 | | 13-m=21 | | 0.06x+0.3=0.06x+0.21+0.09 |